Regional Tourism Development Efficiency - Lenie Fevzievna Khalilova (Universitas Muhammadiyah Sidoarjo, 2020)
This article is about the importance of increasing flow of tourists and its positive impact on the economy of the region as a whole. Today the sphere of tourism in our country is considered as one of the most important sectors of the economy and a significant factor in the development of regions. Solution of many problems in the regions, such as increase of labor employment, attraction of investments, improvement of ecological situation and others are connected with effective functioning of tourism sphere. Domestic and inbound tourism in the process of progress has a positive impact on the formation of the gross domestic product, thus ensuring an improvement in the quality and standard of living of the population. Thus, due to the growth of tourism activities and other service areas, it is possible to solve problems related not only to the improvement of economic indicators, but also to social, environmental and many others. It will be possible to talk about stable development of tourism in the region only when all conditions are fulfilled and companies start working as a whole. In case of deficiencies in one of the spheres, despite the coherence of work, tourism development will fall behind the predicted results. In such a situation the positive dynamics will be temporary. Thus, the main task is to create a single mechanism for all companies connected with this industry.